THE RELATIONSHIP BETWEEN ECHOCARDIOGRAPHIC FEATURES OF MITRAL VALVE AND ELASTIC PROPERTIES OF AORTIC WALL AND BEIGHTON HYPERMOBILITY SCORE IN PATIENTS WITH MITRAL VALVE PROLAPSE - Mehmet Yazıcı; Safinaz Ataoğlu; Sevim Makarç; Melek Kolbas; Enver Erbilen; Sinan Albayrak; Selma Yazıcı; Cihangir Uyan (Archives of Rheumatology, 2002)
The present study was designed to investigate the incidence of benign joint hypermobility syndrome (BJHMS) in mitral valve prolapse (MVP) and correlation between echocardiographic features of mitral valve and elastic properties of aortic wall and Beighton hypermobility score (BHS) in patients with MVP and BJHMS. Forty-six patients with nonrheumatic, uncomplicated and isolated mitral anterior leaflet prolapse (7 men and 39 women, mean age :26.1± 5.9) and 25 healthy subjects (3 men and 22 women, mean age 25.4 ± 4.3) were studied. Patients were divided into two groups according to their BHS (Group I, BHS ≥5; 5; Group II, BHS< 5). Individuals with accompanying cardiac or systemic disease were excluded. Echocaroliographic examination was done to all of the subjects. Presence of BJHMS was evaluated according to Beighton’s criteria. The incidence of BJHMS in patients with MVP was found significantly higher than controls (45.6%, (21/46) vs. 12 % (3/25), p<0.0001). Group I (MVP+BJHMS) had significantly increased anterior mitral leaflet thickness (AMLT, 5.7± 0.6 ve 4.1± 0.5; p<0.001,) maximal leaflet displacement (MLD, 3.8 ± 0.7 vs. 2.9± 0.5; p<0.005) and degree of mitral regurgitation (DMR,17.1 ± 7.2 ve 11.2± 4.4 ;p<0.002) than those of group II. However, index of aortic stiffness (IAOS) was found to be lower ( 17.6± 6.9 vs. 23.9± 7.6; p<0.001) and aortic distensibility (AOD) was found to be higher (0.0035± 0.007 vs. 0.0024± 0.005; p<0.001) in group I. There was significant correlation between AMLT, MLD and DMR and BHS (r=0.57/p=0.007, r=0.55/p<0.009, r=0.51/p<0.01, respectively). In additon, AOD correlated positively with HMS (r=0.53/p<0.005), but index of aortic stifness correlated inversely with HMS (r=-0.49/p<0.007). Conclusion: The incidence of BJHMS in patients with MVP was more frequent than normal population and there was a significant correlation between severity of BJHMS (according to BHS) and echocardiographic features of mitral leaflet and elastic properties of aortic wall .